PENGARUH INTERLOCK DEWAN DIREKSI DAN INTERLOCK AUDITOR EKSTERNAL TERHADAP PENGUNGKAPAN SUKARELA PADA LAPORAN TAHUNAN - Ahmad, Nadya Zulfa; Septiani, Aditya (Diponegoro Journal of Accounting, 2017)
The focus of this study is to examine the effect of board interlock and external auditor towards voluntary disclosure on the annual reports of interrelated firm. Board interlock is a condition where the board directors occupy the same position in other firm. External auditor interlock only occurs if external auditor works in several firms. Voluntary disclosure is a firm’s voluntary information that could help the investors to make a decision.The study population is a non-financial company that is listed on the 2015 period IDX. The type of data is a secunder data from annual report. The total of sample is 48 non-financial firms that use the purposive sampling method. The data analysis used double analysis regression.The results show how board interlock positevely influences the voluntary disclosure on the focal firm. However, external auditor interlock does not influence voluntary disclosure of related companies.